The Influence Of Destination Attractiveness And Visitor Segmentation On Holistic And Conative Outcomes - Easvaralingam, Yalini (2019)
The demand for nature-based tourism globally, highlights the importance of this sector for Malaysia, being a country rich in biodiversity. The challenge faced though is on how to contain mass tourism but still generate revenue. This problem can be overcome by improving the quality of the attractions and examining the influence of visitor segmentation. The objective of this research is to evaluate the influence of destination attractiveness constructs such as core functional attractions, supporting functional attractions, core and supporting psychological constructs and the unique construct on holistic and conative outcomes via the mediating effect of the affective construct. Another objective is to compare the importance of the destination attractiveness constructs with the performance of the constructs in influencing holistic and conative outcomes. The final objective is to identify visitor segmentation criteria and examine the influences of destination attractiveness on holistic and conative outcomes by visitor segmentation. The visitor segmentation constructs are such as travel motivation, familiarity towards nature-based destinations and countrylevel familiarity plus individual-level attraction towards Malaysia. Questionnaires were distributed to 522 visitors of Taman Negara Pahang, Kinabalu National Park and Mulu National Park. Quantitative and qualitative data were collected and analyzed using graphical and descriptive statistics, bivariate tests and multivariate Partial Least Squares Structural Equation Modelling (PLS-SEM).